The unique N-terminal sequence of metallothionein-3 is required to regulate the choice between apoptotic or necrotic cell death of human proximal tubule cells exposed to Cd+2 - Somji, Seema; Garrett, Scott H; Sens, Mary Ann; Sens, Donald A (Toxicological sciences, 2006)
This laboratory has shown that MT-3 expression determines the choice between apoptotic or necrotic cell death in Cd(+2)-exposed human proximal tubule cells. Human proximal tubule cells that express MT-3 undergo necrosis when exposed to Cd(+2), while cells that have no basal expression of MT-3 undergo apoptotic cell death. It was also shown that cells which express MT-3 were more sensitive to Cd(+2)-induced cell death than those having no basal expression. In the present study, site directed mutagenesis was used to determine if the unique N-terminal sequence of MT-3 was required for these activities regarding toxicity and cell death. The results demonstrated that HK-2 cells stably transfected with MT-3 that had been modified by converting the 2 prolines at amino acid positions 7 and 9 to threonines was no longer active in promoting necrotic cell death at lower levels of Cd(+2) exposure. This was shown in comparison to cells containing the wild type MT-3 sequence and blank vector controls as regards the % of DAPI-stained fragmented nuclei, DNA laddering, LDH release, caspase-9, and caspase-3 activation. This study demonstrates that the unique N-terminal sequence of MT-3 is required to elicit an effect on the mechanism of Cd(+2)-induced death of the proximal tubule cell. This is the identical sequence that has been shown to be responsible for the growth inhibitory activity of MT-3 in the neural system.